Monoclonal immunoglobulin G deposits on tubular basement membrane in renal allograft: is this significant for chronic allograft injury?. Issue 4 (16th August 2018) - Sawada, Anri; Kawanishi, Kunio; Horita, Shigeru; Omoto, Kazuya; Okumi, Masayoshi; Shimizu, Tomokazu; Taneda, Sekiko; Fuchinoue, Shohei; Ishida, Hideki; Honda, Kazuho; Hattori, Motoshi; Tanabe, Kazunari; et al.
Abstract: Background: Tubular basement membrane immune deposits (TBMID) has rarely been observed in renal allografts. It is usually found in BK virus nephropathy and immune complex glomerulonephritis; however, its significance is not well understood. We conducted a retrospective clinicopathological study on monoclonal immunoglobulin G (IgG) TBMID. Methods: We studied 7177 renal allograft biopsy specimens obtained from Tokyo Women's Medical University from 2007 to 2015 and performed light microscopic, electron microscopic and immunofluorescence studies. Results: Tubular basement membrane (TBM) deposits of IgG were found in 73 biopsies from 61 patients and the IgG subclass was obtained in 31 biopsies. There were no cases of monoclonal IgA or IgM TBMID. In total, 13 biopsies from 10 patients showed monoclonal IgG TBMID. Of these, seven showed monoclonal IgG1κ TBMID and one each showed monoclonal IgG2κ, IgG2λ and IgG3κ TBMID. Conversely, eight patients showed polyclonal IgG TBMID. In electron microscopy, large granular electron-dense deposits (EDDs) in the TBM were detected in all patients with monoclonal IgG1κ TBMID. EDDs were absent in TBM in patients with monoclonal IgG2κ, IgG2λ or IgG3κ TBMID. Progression of interstitial fibrosis and tubular atrophy (IFTA) was significantly higher in patients with monoclonal IgG1κ TBMID than in those with polyclonal IgG TBMID (P < 0.05). There were no significant differences in the other clinical parameters between monoclonal IgG1κ and polyclonal IgG TBMID. Conclusions: This is the first study of patients with monoclonal IgG TBMID in renal allografts. We found that monoclonal IgG1κ TBMID was associated with EDD formation in TBM and IFTA progression.